Beyond top-down: community co-creation approaches for sustainable dengue vector control - Peter Dambach; Valérie R. Louis; Claire J. Standley; Carlos Alberto Montenegro-Quiñonez (Taylor & Francis Group, 2024)
Dengue fever, a mosquito-borne viral illness transmitted by Aedes mosquitoes, continues to be a significant public health burden in tropical and subtropical regions. Traditional vector control methods, primarily reliant on insecticides and larvicides, face challenges because of emerging insecticide resistance and limited community engagement. This narrative review explores co-creation as a collaborative approach to dengue control, where communities actively participate in designing and implementing solutions. Through an examination of existing literature, we discuss the rationale for co-creation, the various methods employed, evidence for effectiveness, challenges, and other items. Findings from previous studies suggest that co-creation can empower communities by fostering a sense of ownership and responsibility for dengue control efforts. Using local knowledge and insights, co-creation approaches have also been shown to identify and address specific community needs and preferences, leading to more contextually relevant interventions. Additionally, co-creation initiatives have demonstrated success in promoting behavior change within communities, leading to increased uptakes of preventive measures such as proper waste management and use of personal protective measures. However, challenges such as building trust and collaboration, addressing power dynamics, and ensuring long-term sustainability remain critical factors that are essential to foster collaboration, empower communities, and develop sustainable strategies for dengue control in affected regions.